The invertebrates of temporary rivers in the Eastern Cape, South Africa - Uys, Amanda Cloete (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1998)
Temporary rivers in dryland regions are subject to highly variable and unpredictable rainfall and flow, and are considered unstable systems relative to perennial rivers of temperate zones. Little is known of the ecology of South Africa's temporary rivers, despite their abundance. The research presented focusses on the aquatic invertebrates inhabiting intermittently-flowing rivers in the 'arid corridor' of the Eastern Cape, South Africa. The major aims of the work were: to investigate which invertebrates inhabit these rivers, how the fauna is affected by environmental variability at various spatial and temporal scales, whether or not a characteristic fauna can be associated with these rivers or the hydrological phases which characterise them, and to establish to what extent faunal overlap occurs between different temporary rivers and between natural and modified temporary and perennial rivers. Research results indicate that the fauna of the Eastern Cape temporary rivers shows little structure at the scales of investigation, and that communities are generally non-equilibrial in character. The major forces shaping the biota are considered to be physical rather than biological, and the most important of these are: present and antecedent hydrological conditions and their duration; time of year; and biotope character, extent and heterogeneity. Three groups of fauna were identified as inhabitants of the temporary rivers: 'residents', 'facultative taxa' and 'opportunist colonists'. Taxa were tentatively allocated to these groups. Faunal resemblance was fairly high in Eastern Cape temporary rivers at the level of family, but not at more detailed taxonomic levels. A comparison between faunas of temporary and perennial rivers in different regions of South Africa illustrated the influence of geographical location on diversity. Within regions, however, there was no indication that perennial rivers were more diverse than intermittent rivers. The relatively high diversities in temporary rivers in this study are attributed at least in part to the heterogeneity in surface water conditions over time. A conceptual framework envisioning a continuum between perennial and temporary rivers is proposed as a basis for ongoing research into these rivers. A supporting terminology for the range of river flow types in South Africa is presented.
Keywords: Rivers -- South Africa -- Eastern Cape; Stream ecology -- South Africa -- Eastern Cape; Freshwater invertebrates -- South Africa -- Eastern Cape